(untitled) (Analysis in Theory and Applications, 2014)
Let P(z) be a polynomial of degree n and for any complex number α, let D_αP(z)=nP(z)+(α -z)P'(z) denote the polar derivative of P(z) with respect to α. In this paper, we obtain certain inequalities for the polar derivative of a polynomial with restricted zeros. Our results generalize and sharpen some well-known polynomial inequalities.